Enhancement mechanism for boron removal at high anodic polarization potential during electrocoagulation using iron-based materials. Issue 2 (April 2022) - Yao, Guangyuan; Zeng, Fanlai; An, Zhiwei; Li, Hao; Zhu, Tianzhen; Fang, Jing
Abstract: In the process of oil and gas exploitation, a large amount of fracturing wastewater is usually produced. Removal of boron from hydraulic fracturing wastewater can promote the recycling of water resources. Electrocoagulation is an environmentally friendly method for boron removal, which has attracted wide attention in recent years. In this work, electrochemical and chemical methods were used to analyze the difference of the performance of iron anodes in boron removal, and the role of anode polarization in the process of boron removal was discussed. The results show that for Q235 CS, the boron removal efficiency increases from 7% to 16% as the potential moves from R1 (− 0.5 to (− 0.2) V) to R3 (0.5–0.8 V). Similarly, for 304 SS, maximum boron removal efficiency can be achieved at R3. Strong anodic polarization not only allows direct dissolution of Fe 3+ ions, but also promotes the formation of oxides. Both processes are beneficial to the formation of iron products and have good coagulability. This work provides a new perspective for the research of electrocoagulation technology and is beneficial to the improvement of existing technology. Graphical Abstract: ga1 Highlights: The electrochemical method is used to increase the boron removal effect in fracturing wastewater and promote its recycling. The effect of different iron based electrodes on boron removal by electric flocculation was systematically studied. The controlled potential method is proposed to improve the removal effect of boron by electric flocculation. The enhancement mechanism of anode potential on boron removal by electric flocculation was described.